BACTERIAL CELL SUPPLIES AND CAPSULES (Scientific journal of the Fergana State University, 2024)
In this article, bacteria are single-celled microorganisms. They are different form and have a complex structure, which determines the diversity of their activities. The outer layer of bacteria is very thin, surrounded by the clear, thickened section of bacteria, and producing water to itself, forming a capsule, and maintaining a capsule from toxins.